Residential areas with apartment houses: analysis of the condition of buildings, planning issues, retrofit strategies and scenarios - Raslanas, Saulius; Alchimovienė, Jurgita; Banaitienė, Nerija (International Journal of Strategic Property Management, 2011)
Modernisation of apartment houses is a particularly relevant issue both in Lithuania and many other countries. To make it more efficient, the modernisation of apartment houses must be integrated–an entire block or residential area must be renovated and the principles of sustainable development must be followed. This article dwells on the issues related to retrofit planning in residential blocks/areas and analyses the condition of apartment houses and their environment. The article also proposes strategies for retrofit of residential areas with apartment houses. The strategies aim to improve the living standards and the quality of environment, to cut energy consumption and Co2 emissions, to maintain mixed social structure, to integrate new buildings into the existing environment in a sustainable manner, to develop an urban centre of a residential area as a functioning part of the city, to develop democratic planning and to seek close cooperation of modernisation partners. The scenarios based on relevant strategies must define the measures of retrofit, their priority and their potential effect. First Publish Online: 4 Jul 2011